AUTOMATION OF PROGRAMMING TRAINING IN THE CONTEXT OF CONSTRUCTION. HIERARCHICAL PROGRAM STRUCTURE (Journal of Information Technologies in Education (ITE), 2011)
The article describes the research and program development in the field of application of graphs in the learning process and at testing stage by testing. The paper describes the approaches to creating the effective test software, operating objectives, which include the construction of hierarchical structures. The description of new author's authentic software, which is a prototype that implements the innovative ideas of using graphs in testing students, and generally implements support of working with hierarchical structures.
Keywords: graphs; information technology; software; testing